Analisis Kepemimpinan, Disiplin Kerja, Motivasi, dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Dinas Kebudayaan dan Pariwisata Pemerintah Kota Semarang - Amara Yulaida Fitria; Artha Febriana; Sih Darmi Astuti; Nanda Adhi Purusa (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
The purpose of this research is to examine how the leadership, work discipline, motivation, and environment of the Semarang City Culture and Tourism Office affect the performance of its workers. The researchers in this study used a quantitative method, gathering data via interviews and questionnaires. The study used a saturation sampling method. Information was gathered from 69 respondents. The data was analyzed using Smart PLS software, which includes features including hypothesis testing, internal model analysis, and external model analysis. Employee performance was positively affected by leadership style, work discipline, and the work environment, while motivation was shown to have no such impact.